Procedure for the practical and economic integration of solar PV energy in the city of Bogotá - N.A. Galvis Barrera (Elsevier, 2021)
Photovoltaic (PV) solar technology is becoming progressively widespread at both urban and rural levels, thanks to the worldwide costs falling of the solar panels. This work presents a methodology for integrating photovoltaic solar systems at the residential level in Bogotá, Colombia, and the analysis of Law 1715–2014 and its implications in the renewable energy incentives. The technical and economic aspects to supply the energy demand of residential consumers of strata 2 and 3 of the Colombian capital were analyzed. The study defines two financing scenarios: one including the economic incentives of Law 1715 of 2014 and the other without considering them. These scenarios encompassed four sub-scenarios. Two sub-scenarios were designed to cover the energy consumption of 1 consumer of category (stratum) two and one consumer of category 3, and the other two sub-scenarios represented the coverage of the demand of all subscribers in each category. The main results indicate that covering from 10% to 100% of the power requirement of a single consumer in category two allows annual savings ranging from USD 29.72 and USD 293.27, respectively; while covering from 10% to 100% of the requirement of a single consumer of category 3 allows annual savings ranging from USD 29.62 and USD 296.18 respectively. The environmental analysis determined that the CO2 emissions avoided in sub-scenarios 1 and 2 in the next 25 years were 20.41 and 20.39 tons of CO2 equivalent.